If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 1y + 2 Reorder the terms: 3x = 2 + 1y Solving 3x = 2 + 1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0.6666666667 + 0.3333333333y Simplifying x = 0.6666666667 + 0.3333333333y
| -9+2.5y-0.7+1+6.4y= | | 4(p+7)=36+5p | | 7z+8=6z | | (2-7x)=(2x+1) | | 4(x+7)=36+5p | | 18-12x=-22-7x | | 3p(r+1)=7r-8t | | 7p-3=34 | | 12-36x-6x-24=-12 | | 5(9x-5)+12x= | | g(2)=7x-4 | | 2x+3y=4z-3xy | | 5a+35-12a-3=12-12a | | 2+3(-8n+6)=116 | | 125+15m=800 | | 10x+90=8x | | 3+(6x+4)=9 | | 2x+x-250=2858 | | 3(3Y-5)Y=-15 | | 8y-5x=27 | | 3a+15=3(a+5) | | 7=8(x+4)-2x | | 13-8b=-4b+5 | | 460g+g=11g | | 4-3(2-y)=y-2(3y-7) | | 18x+(-8+23)=5x(3+4) | | x-3x=60 | | -75+W=0 | | 1.2a+1.2a=a+1 | | x+2x=1.30 | | 4y+14+3y=5y-2 | | 2x-3=5c-1 |